HALOGENETIC PROPERTIES OF IRRIGATED MEADOW SAZ SOILS (Scientific journal of the Fergana State University, 2026)
The article analyzes the halogenetic properties of irrigated meadow saz soils and the processes of their formation. The amount of salts in the soil, the degree of salinity, the distribution of salts, and the processes of salt migration have been determined. According to the research results, the redistribution of salts under irrigation conditions affects the genetic horizons of the soil and activates halogenetic processes. Therefore, a thorough study of the halogenetic characteristics of irrigated meadow saz soils is of great importance for the effective implementation of reclamation and agrotechnical measures.